Cost Structure and Efficiency at PT.Bersama Lemindo Abadi : case study - Helmy Ivan Taruna (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2019)
Indonesia still considered as good market for this adhesive industry. This creates high competition among the players. The intensity of competition among the existing competitors in the market is high, because there are number of small, equal or even higher competitors. Industry is also growing, even though customer have low switching cost. However fixed cost are high. resulting huge production and reduction in prices. These situations make the reasons for advertising wars, price wars, modifications, ultimately costs increase and it is difficult to compete.